The dimensionality of the Edinburgh Handedness Inventory: An analysis with models of the item response theory - Büsch, D.; Hagemann, N.; Bender, N. (Laterality: Asymmetries of Body, Brain and Cognition, 2010)
Handedness is frequently measured with sum scores or quotients taken from laterality questionnaires like the Edinburgh Handedness Inventory (EHI). In classical test theory such data cannot be used to confirm either the unidimensionality (i.e., quantitative differentiation with the poles left-handed and right-handed) or multidimensionality (i.e., typological differentiation between left-, right-, and mixed-handers) of this personal characteristic. This study uses item response theory models to test the construct validity of the EHI on an item level in order to gather empirical support for the differentiation of handedness as well as the appropriateness of the items and the response format. The EHI was given to 540 participants (303 male and 237 female) aged 17-37 years. Results of mixed-Rasch analyses revealed that the best model was a two-class solution; that is, left- and right-handers (types) with quantitative differences between persons. Hence, unlike earlier model tests, this rejects both the unidimensionality of the handedness construct and the need to consider so-called mixed-handers. It is proposed that mixed-Rasch analyses should be applied more frequently to test the construct validity of other as well as more extensive handedness questionnaires.